2
$\begingroup$

Let $f$ and $g$ the polynomials

$$f(x) = (x+1)^{2n-1}+(-1)^n(x+2)^{n+1}\qquad\text{and}\qquad g(x) = x^2 + 3x + 3$$

How do I demonstrate that $g$ divides $f$? I tried finding the roots of $g$ then testing them for $f$, it didn't work ...

I also wrote g as $(x+1)^2 + x + 2$ but I couldn't get anywhere.

$\endgroup$
  • $\begingroup$ Your second approach looks promising... Is it possible to separate even and odd cases of $n$? Have you worked with small $n$, or tried induction? $\endgroup$ – abiessu Mar 28 '16 at 13:26
  • $\begingroup$ Another approach might be to rewrite using $y=x+1$ and see what happens. $\endgroup$ – abiessu Mar 28 '16 at 13:31
  • 1
    $\begingroup$ I did this $(x+1)^2 + x + 2 = 0 <=> (x+1)^2 = (-1)(x+2) |^n <=> (x+1)^{2n} = (-1)^n(x+2)^n$ but i don't know now what to do $\endgroup$ – oren revenge Mar 28 '16 at 13:32
2
$\begingroup$

Let $r$ be any of the two roots of $g$; since $g(r) = (r+1) (r+2) + 1$, obviously $r+1 \ne 0$ and we get $r+2 = -\frac 1 {r+1}$. To have $g \mid f$ we should have $f(r) = 0$, so let us compute $f(r)$.

Since

$$f(r) = (r+1)^{2n-1} + (-1)^n (r+2)^{n+1} = (r+1)^{2n-1} + (-1)^n \left(- \frac 1 {r+1} \right)^{n+1} = \\ (r+1)^{2n-1} - \frac 1 {(r+1)^{n+1}} = \frac {(r+1)^{3n} - 1} {(r+1)^{n+1}} ,$$

let us finally show that $(r+1)^{3n} - 1 = 0$. To do this, notice that

$$(r+1)^3 = r^3 + 3r^2 + 3r + 1 = r g(r) + 1 = 1 ,$$

whence it follows that $(r+1)^{3n} - 1= \left((r+1)^3 \right)^n - 1 = 1^n - 1 = 0$, as desired.

This shows that indeed $f(r) = 0$ for each of the two roots $r$ of $g$, so indeed $g \mid f$.

$\endgroup$
0
$\begingroup$

For $f_n(x) = (x+1)^{2n-1}+(-1)^n(x+2)^{n+1}$ with $g(x) = x^2+3x+3=(x+1)^2+x+2$, first consider $n=1,2$:

$$f_1(x) = x+1-x^2-4x-4 = -x^2-3x-3\\ f_2(x) = (x+1)^3+(x+2)^3=(2x+3)\left((x+1)^2-(x+1)(x+2)+(x+2)^2\right)\\ =(2x+3)(-(x+1)+(x+2)^2)=(2x+3)(x^2+3x+3)$$

So we have that $g(x)\mid f_1(x),\ g(x)\mid f_2(x)$. It appears that a useful way to approach the question is to show that we end up with something either of the form $(x+1)^2+(x+2)$ or $(x+2)^2-(x+1)$. To this end, with $y=x+1\to g(y)=y^2+y+1$, consider that we have

$$f_n(y) = y\left(y^2\right)^{n-1}+(-1)^n(y+1)^2(y+1)^{n-1}\\ =(-1)^n(y^2+y+1)(y+1)^{n-1}+y\left((y^2)^{n-1}+(-1)^n(y+1)^{n-1}\right)$$

For even $n$, $(y^2)+(y+1)$ is always a factor of $(y^2)^{n-1}+(-1)^n(y+1)^{n-1}$ (just as $a+b\mid a^{2n-1}+b^{2n-1}$). Now the only remaining issue is to determine whether $(y^2)+(y+1)$ is a factor of $f_n(x)$ for odd $n$. But we see that for odd $n=2m+1$, $(y^2)^{n-1}+(-1)^n(y+1)^{n-1}$ is a difference of squares, and therefore factors as

$$\left((y^2)^m-(y+1)^m\right)\left((y^2)^m+(y+1)^m\right)$$

If $m$ is odd, we are done; if $m$ is even, we can split the left-hand term as a difference of squares again; we can repeat as needed until we have a sum with odd outer exponents. Therefore $g(y)\mid f_n(y)$ and thus $g(x)\mid f_n(x)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.